A fresh look at chemical fossil extraction - McCrae, Ceri; Potze, Stephany (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2007)
In this age of microtechnology, now more than ever before, detail is indispensable. In the past, the damage to fossils during retrieval, preparation and storage was an accepted downfall of the scientific process. With the increasing use of advanced techniques, which rely on high-resolution applications such as scanning electron microscopes and microtomography, there is a definite need to improve on the actual fossil extraction methods currently used. The aim of this work is to achieve an ideal method of extraction where the fossil is retrieved in its entirety without adding or taking away any evidence whatsoever.